Potential Association Between Anabolic Androgenic Steroid Abuse and Pituitary Apoplexy: A Case Report - Andriuskeviciute, Agne; Cossu, Giulia; Ameti, Adelina; Papadakis, Georgios; Daniel, Roy Thomas; Dunet, Vincent; Messerer, Mahmoud (Frontiers in Endocrinology, 2022)
Introduction Pituitary apoplexy (PA) is a rare, and potentially life-threatening condition, caused by hemorrhage or infarction into the pituitary gland with a rapid expansion of the contents of the sella turcica, associated with sudden intense headache, neurological and endocrinological deterioration. The identification of risk factors is crucial for prevention and optimal management. Herein we report a case of PA occurring 1 month after the initiation of anabolic androgenic steroid abuse for bodybuilding. Case Report A 40-year-old male patient presents with abrupt onset headache associated with left partial third cranial nerve palsy. The MRI shows a sellar lesion involving left cavernous sinus with a heterogenous anterior aspect of the lesion with hemorrhagic zones in favor of PA. Endocrine work-up shows high testosterone level in patient who was using exogenous testosterone without a medical prescription for a month. Conclusion We report a case of PA of a pituitary neuroendocrine tumor occurring shortly after AAS. The association between PA and AAS should be considered as a potential risk.